2008
DOI: 10.1080/10253890701638303
|View full text |Cite
|
Sign up to set email alerts
|

Selective blockade of 5-HT2A receptors attenuates the increased temperature response in brown adipose tissue to restraint stress in rats

Abstract: Previous studies have demonstrated that 5-HT2A receptors may be involved in the central control of thermoregulation and of the cardiovascular system. Our aim was to test whether these receptors mediate thermogenic and tachycardiac responses induced by acute psychological stress. Three groups of adult male Hooded Wistar rats were instrumented with: (i) a thermistor in the interscapular area (for recording brown adipose tissue temperature) and an ultrasound Doppler probe (to record tail blood flow); (ii) tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Restraint in rodents clearly elicits an adrenergic, hypermetabolic response (Nagasaka et al 1979). Ootsuka et al (2008) found a marked rise in temperature of the interscapular brown adipose tissue during physical restraint. This would suggest that restraint-induced activation of thermogenesis in brown adipose tissue contributes to the overall rise in core temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Restraint in rodents clearly elicits an adrenergic, hypermetabolic response (Nagasaka et al 1979). Ootsuka et al (2008) found a marked rise in temperature of the interscapular brown adipose tissue during physical restraint. This would suggest that restraint-induced activation of thermogenesis in brown adipose tissue contributes to the overall rise in core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Ootsuka et al (2008) made continuous measurements of tail blood flow in rats subjected to 30 min of physical restraint and found a transient reduction when first placed in the restrainer, followed by recovery and elevation in blood flow after about 20 min of restraint. We cannot reconcile a rise in total tail blood flow and reduction in the HLI from the tail observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shibata and Nagasaka (25) used a subtraction method similar to ours to estimate iBAT thermogenesis and demonstrated that the increase they observed after a 2-min immobilization was abolished by sympathectomy. Ootsuka et al (23) used a more common restraint paradigm that lasted 30 min; however, body temperature was not subtracted, and no propranolol injection or sympathectomy was made to verify the iBAT origin of the local temperature increase. Clearly, further work is needed to clarify the role of BAT in the hyperthermic response of different forms of psychological stress.…”
Section: Discussionmentioning
confidence: 99%